PVD improvement of reconstituted soft clay with and without electro-osmotic consolidation - Patawaran, Ma. Aries B.; Bergado, Dennes T.; Balasubramaniam, A.S.; Guey, Lin Der; Asian Institute of Technology Partial Scholarship (Bangkok : Asian Institute of Technology, 1998)
The effect of prefabricated vertical drains (PVD) with and without electro-osmosis on reconstituted soil was investigated. The effect of increasing surcharge while maintaining the same voltage gradient was also examined. The test was conducted on reconstituted soil from AIT. An initial 50 KPa pressure was applied until 90% consolidation. Prefabricated drains L:Ut to 20m::n width were then installed at 20cm spacing in a square pattern. The load was increased to 75 KPa and the effect of the drains was observed. Afterwards, electro-osmosis was applied using a voltage gradient of 80 V /m while maintaining the same overburden pressure . The surcharge was then increased to 82.5 KPa while the voltage gradient remained constant. Test results indicate that the reduction in the water content of the soil was almost the same for both PVD with and without electro-osmosis. An increase in the overburden pressure however, can triple the moisture reduction. Application of electro-osmosis brought about an increase in the shear strength at the anodes. Larger settlements and smaller differential settlements under higher overburden pressures was observed with bigger values occurring at the anodes. An increase in the liquid and plastic limit was also discovered. It was also found out that there is a decrease in the void ratio of the soil with higher values observed at the anodes than at the cathodes.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1998
Keywords: Vertical drains; Soil consolidation test